Investigasi Awal Perilaku Pengguna Terhadap Penerimaan Aplikasi e-Transportasi di Kabupaten Nganjuk: Studi Kasus Aplikasi HeehJek - Tri Lathif Mardi Suryanto, (ReTII, 2019)
Abstract E-Trasnportasi is a transportation application service that provides pick-up and delivery of service products through internet-based applications. Today, E-Trasnportasi are not only in urban areas but have entered rural areas. HeehJek is one of the E-Trasnportasi Applications that appear in Nganjuk Regency with nuances of local wisdom. The existence of cultural development in the community, from riding conventional transportation to switching to on-line transportation becomes an interesting phenomenon to get special attention on research into the behavior of users of the HeehJek application. As a preliminary study this research uses a quantitative method with a conceptual approach to technology acceptance models. Respondents were taken as many as 300 by cluster sampling, which then performed SEM-PLS analysis. The results of this study address the acceptance of the Nganjuk community towards HeehJek due to the belief, ease, and usefulness of the HeehJek application in supporting daily activities carried out.